PENYELESAIAN KASUS PELANGGARAN HAK ASASI MANUSIA BERAT DI INDONESIA OLEH KOMISI NASIONAL HAK ASASI MANUSIA DITINJAU DARI KEWENANGANNYA (STUDI KASUS TIMOR-TIMUR) - Viddy Firmandiaz; Jadmiko Anom Husodo (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
This study analyzes the settlement of serious human rights violations by Komnas HAM in terms of its authority to the East Timor case studies. This study is a prescriptive normative law that aims to analyze the effectiveness of the authority of Komnas HAM in the resolution of serious human rights violations and provide solutions for problems that were examined by the author. This study uses primary data in the form of an investigation report of the East Timor Human Rights Violation Investigation Commission and secondary data in the form of primary legal materials and secondary law. Data collected through library research to find secondary data using primary legal materials, secondary, and tertiary. In writing this law, the writer uses the statutory approach, the concept approach, the case approach, and the historical approach. The results of this study show that the authority of Komnas HAM to be ineffective causing delays resolution of cases of serious human rights violations in Indonesia, which according to the author due to the weak legitimacy of institutions, lack of subpoena authority of Komnas HAM and disharmony with the Attorney General.